Ramps & pathways a constructivist approach to physics with young children - DeVries, Rheta (National Association for the Education of Young Children, 2011)
Provides an introduction to constructivist physics with classroom examples illustrating how children construct knowledge. Shows how to promote children's scientific reasoning by engaging them in active experimentation.